Tomada de decisão em opções estratégicas : proposta de um método de avaliação sistêmico e dinâmico - Morandi, Maria Isabel Wolf Motta (Universidade do Vale do Rio dos Sinos, 2017)
Strategic decisions aim to operationalize the company's strategy in order to reach its goals, which, although it may be of multiple natures, seek to increase the returns for the shareholders and the value of the company itself. The capital budgeting process, more specifically the project evaluation and selection stages, provides the basis for selecting the highest return options. However, the traditional methods present gaps, especially regarding the consideration of the systemic impacts caused by the exercise of a strategic option, and the uncertainties present in the strategic decision process. In this sense, the objective of this research is the proposition of a method to evaluate the strategic options in a systemic and dynamic way, that is, that considers how the reactions of the actors and the uncertainties impact on the result of the chosen option. Design Science Research was the method selected to conduct this research. The artifact is the strategic options evaluation method, which aims to calculate the systemic and dynamic NPV, that is, the taking into account the reaction of the actors in the various future scenarios. The developed method was applied in a mining company that satisfy both the construction heuristics and the contingency heuristics identified in the artifact construction process. This application allowed to satisfactorily evaluate the proposed method, as well as to identify possible refinements. From the results, it was possible to verify both the theoretical and the managerial contributions. From the theoretical point of view, the main contribution is the concept and the construct of the systemic and dynamic NPV. A secondary contribution is a toll to evaluate, in a quantitative way, the significance of the critical uncertainties in the formulation of the scenarios. From the managerial point of view, the possibility of systematically and dynamically evaluating the strategic options, evaluating the synergistic effects between them and their robustness in the different scenarios, constitutes a contribution to the decision-making process.
Keywords: Decisões estratégicas; Pensamento sistêmico; Cenários; Dinâmica de sistemas; Strategic decision making; Systems thinking; Scenarios; Systems dynamics; ACCNPQ::Engenharias::Engenharia de Produção